Expert consensus on the clinical application of artificial iris: consensus - Yan, Hua; Chen, Wei; Zhao, Zhenquan; Guo, Tao; Li, Jun; Ji, Yinghong; Yang, Jin; Xiao, Xuan; Huang, Yanming; Snyder, Michael; Mayer, Christian; Derveaux, Thierry; et al. (Journal of evidence based medicine, 2026)
Objective To establish evidence-based guidance to standardize the clinical application of artificial iris implantation in patients with iris defects. Methods A systematic literature search was performed following evidence-based consensus development standards. Eighteen international experts participated in a Delphi process to define six core clinical issues. Evidence was screened, extracted, evaluated and integrated. Recommendations were formulated through iterative expert review. Results We established six key clinical issues related to artificial iris implantation and evidence-based recommendations to address critical gaps in clinical practice. Key outcomes included standardized criteria for indications, contraindications, and type of artificial iris selection, key aspects of surgeon-patient communication, surgical management principles and critical techniques, comprehensive perioperative care protocols, and strategies for managing long-term postoperative complications associated with artificial iris implantation. Conclusions This consensus standardizes artificial iris implantation through six evidence-based recommendations. It provides a standardized protocol for safe clinical implementation to restore visual function and cosmetic integrity in patients with iris defect.